Strategy For Collection and Distribution of Infaq Shodaqoh Zakat Funds At Amil Zakat Institution (LAZ) Sahabat Mustahiq Malang Branch - Nabilah, Diananda Hanan; Hakim, Rahmad; Hakim, Arif Luqman; Fanani, Ahmad (Perisai : Islamic Banking and Finance Journal, 2023)
The strategy for collecting and distributing zakat, infaq, and shodaqoh funds is important and implemented properly. Especially in areas such as Malang Raya which has the highest number of muzakki in East Java. The purpose of this study is to conduct an in-depth analysis of the strategy for collecting and distributing zakat, infaq, and shodaqoh funds (ZIS) at the Amil Zakat Institute (LAZ) Sahabat Mustahiq Malang. This research is a qualitative research with a case study approach. Data collection techniques in this study were observation, interviews, and documentation. Data analysis techniques used in this study are data collection, data condensation, data presentation, and drawing conclusions. The results of the study indicate that there are two kinds of strategies in raising funds, namely direct and indirect. Direct is a strategy that is carried out directly between amil zakat institutions and muzakki or donors. Direct activities in the form of direct mail via whatsapp, direct meetings with potential muzakki, zakat outlets and portfolios. The indirect strategy is a strategy that is carried out indirectly between amil zakat institutions and muzakki or donors. Indirect activities are in the form of collaborating with other LAZ institutions, agencies or institutions, activating social media, magazines, websites, digital platforms and through Friends of Inspirational Action (SAINS) volunteers. In the strategy for distributing zakat, infaq, shodaqoh funds at LAZ Sahabat Mustahiq Malang, there is a pattern of distribution of zakat infaq shodaqoh funds, namely traditional consumptive, creative consumptive, traditional productive, creative productive but in the distribution of infaq and shodaqoh zakat funds to 8 asnaf that have been listed in the Qur'an 'an, LAZ Sahabat Mustahiq Malang prioritizes fakir, poor, zakat manager, sabilillah and ibn sabil only.